Acetazolamide-mediated carbonic anhydrase inhibition suppresses human peripheral blood mononuclear cell proliferation via G1/S cell cycle arrest - Syazili Mustofa; Mohamad Sadikin; Sarmoko (Indonesian Society for Biochemistry and Molecular Biology, 2026)
Background: Carbonic anhydrase (CA) regulates intracellular CO₂/HCO₃⁻ homeostasis and supplies carboxyl donors for the sixth step of de novo purine biosynthesis. Disruption of this step is predicted to impair nucleotide pool accumulation and arrest cell cycle progression. Objective: This study investigated whether CA inhibition by acetazolamide suppresses T lymphocyte proliferation. Methods: Human peripheral blood mononuclear cells (PBMCs) were stimulated with phytohemagglutinin (PHA, 1% v/v) or interleukin-2 (IL-2, 10 ng/mL). Acetazolamide was applied at 6.25–50 μM. Cell viability, DNA synthesis, and cell cycle distribution were assessed using WST-1 assay, BrdU incorporation, and propidium iodide flow cytometry, respectively. Results: Acetazolamide reduced PBMC viability and DNA synthesis dose-dependently in both PHA- and IL-2-stimulated cultures (p < 0.05). IL-2-stimulated cells showed greater sensitivity, with significant inhibition at 12.5 μM versus 25 μM for PHA-stimulated cells. Flow cytometry revealed G1/S arrest in all treated groups: S phase decreased from 8.52% to 3.82% (PHA) and from 1.27% to 0% (IL-2) at 50 μM, with G2/M uniformly suppressed to ≤0.57%. Conclusion: Acetazolamide suppresses PBMC proliferation through G1/S arrest, consistent with CA inhibition depleting CO₂/HCO₃⁻-dependent carboxyl donors required for de novo purine synthesis.